FENOMENA ALIH KODE DAN CAMPUR KODE DALAM VIDEO YOUTUBE MENJADI MANUSIA - Makasambe, Jeansi; Djeinnie Imbang; Vivi Nansy Tumuju (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe forms of code-switching and code-mixing, as well as to determine the reasons or factors behind the use of code-switching and code-mixing found in videos on the youtube channel Menjadi Manusia. The research method used in this study is qualitative. Data collection used the observation method and Sudaryanto's note-taking technique. Data analysis used the matching method, specifically the translational matching method. Code switching occurred from Indonesian to English and vice versa. The results of this study found a total of 128 utterances consisting of 51 instances of intra-sentential switching, only 1 instance of inter-sentential switching, and 3 instances of emblematic switching. Furthermore, intra-sentential mixing code-mixing forms were found in a total of 61 utterances, while intra-lexical mixing code-mixing forms were found in a total of 12 utterances. The causes of code-switching and code-mixing were found to be due to factors such as discussing certain topics, repeating for clarification, and the speaker's personal involvement and desire to be understood well. Keywords: code switching, code mixing, youtube